1962
DOI: 10.1103/physrev.127.1892
|View full text |Cite
|
Sign up to set email alerts
|

Electron Spin Resonance of Hydrogen Atoms in CaF2

Abstract: We report the results of a detailed investigation of the electron spin resonance of a hydrogen atom in an interstitial position in CaF 2 . The following aspects of the problem are treated in detail: (1) apparatus and sample preparation; (2) a spin Hamiltonian with four parameters describing the g value and hfs of the hydrogen atom with the eight equivalent fluorine nuclei surrounding it; (3) the electron-nuclear double resonance (ENDOR) spectrum and the resonance linewidth; and (4) an attempt to calculate the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
31
0
2

Year Published

1964
1964
2014
2014

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 181 publications
(33 citation statements)
references
References 24 publications
0
31
0
2
Order By: Relevance
“…The Rare Earths were added to the melt as the oxide or fluoride in concentrations from 0.02 to 0.5 atyo. Samples typically 1 to 2 mm in thickness were cleaved from the as-grown crystals and treated with hydrogen or deuterium in the manner described by Hall and Schumacher [3]. After diffusion, the samples were ground and polished where necessary to remove surface damage prior to optical examination.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The Rare Earths were added to the melt as the oxide or fluoride in concentrations from 0.02 to 0.5 atyo. Samples typically 1 to 2 mm in thickness were cleaved from the as-grown crystals and treated with hydrogen or deuterium in the manner described by Hall and Schumacher [3]. After diffusion, the samples were ground and polished where necessary to remove surface damage prior to optical examination.…”
Section: Methodsmentioning
confidence: 99%
“…ion, in which case the symmetry of both ions is reduced to C4". Such It is now well known that a fraction of the F-ions in fluorite crystals may be replaced by H-ions by means of the diffusion process described by Hall and Schumacher [3]. It has also been shown that when trivalent ions are present in oxygen-free crystals, interstitial H-ions are introduced.…”
Section: Introductionmentioning
confidence: 97%
“…Because the H -ion has a differe nt mass , polarizability, and interac tion with its neighborin g ions than has the anion which it replaces, th e U ce nter c hanges both the phonon spectrum and th e optical prope rties of its host crystal. Changes in th e phonon spectrum include ne w features at e nergies substantially greater than the energies df the optic phonons of the host lattice [1][2][3][4][5][6][7][8][9][10][11]. 1 Changes in the optical properties include a c harac teristi c electronic absorption band, the V band , in the ultraviole t region [12][13][14][15][16][17][18][19][20] and are the concerns of this paper.…”
Section: Introductionmentioning
confidence: 99%
“…The X-irradiation of these crystals produces hydrogen and deuterium atoms on interstitial and substitutional sites. The EPR spectra are well known (1 …”
mentioning
confidence: 99%